2012
DOI: 10.1177/147323001204000335
|View full text |Cite
|
Sign up to set email alerts
|

Arg555Gln Mutation of TGFBI Gene in Geographical-Type Reis—Bücklers Corneal Dystrophy in a Chinese Family

Abstract: In this Chinese family an R555Q mutation of the TGFBI gene was associated with RBCD. As the RBCD phenotype is usually associated with an R124L mutation, this novel genotype-phenotype correlation may prompt further investigation of Bowman's layer corneal dystrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The R124L mutation is also a common mutation type. In other atypical cases, R125H, R555Q, R555W and a few mutations at the R124C, G623D, H572R and H626P sites have also been reported [19][20][21][22][23][24][25][26][27] . Our study also found that the CD of this pedigree had high incidence, early onset age, severe condition and high recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…The R124L mutation is also a common mutation type. In other atypical cases, R125H, R555Q, R555W and a few mutations at the R124C, G623D, H572R and H626P sites have also been reported [19][20][21][22][23][24][25][26][27] . Our study also found that the CD of this pedigree had high incidence, early onset age, severe condition and high recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we kept Bowman's membrane and found that corneal epithelialization occurred in 1 week, which was as quick as human cornea transplantation. A regular arrangement of collagen fibrils was observed in normal clear corneal stroma, while collagen fibrils were not regularly arranged and disorganized in opaque corneal stroma (Piao, Zhou, Wu, & Chu, ; Wei et al, ). The regularity of collagen fibrils was assessed by distances between collagen fibers and the diameter of fibers using TEM.…”
Section: Discussionmentioning
confidence: 99%